2022
DOI: 10.1038/s41417-022-00466-1
|View full text |Cite
|
Sign up to set email alerts
|

Description and optimization of a multiplex bead-based flow cytometry method (MBFCM) to characterize extracellular vesicles in serum samples from patients with hematological malignancies

Abstract: Extracellular Vesicles (EVs) are membranous vesicles produced by all cells under physiological and pathological conditions. In hematological malignancies, tumor-derived EVs might reprogram the bone marrow environment, suppress antileukemic immunity, mediate drug resistance and interfere with immunotherapies. EVs collected from the serum of leukemic samples might correlate with disease stage, drug-/immunological resistance, or might correlate with antileukemic immunity/immune response. Special EV surface protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Typical cup-shaped appearance of serum EVs were identied by TEM and EV concentrations and size distribution proles of puried serum EV samples from H and AML patients by fNTA, as shown before. 22 In this manuscript, we focused on the quantitative and qualitative assessment of EV surface characteristics via MBFCM and especially the characterization of the EV-derived miRNA cargo by RNA-Seq to evaluate their potential as biomarkers in AML samples compared to healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical cup-shaped appearance of serum EVs were identied by TEM and EV concentrations and size distribution proles of puried serum EV samples from H and AML patients by fNTA, as shown before. 22 In this manuscript, we focused on the quantitative and qualitative assessment of EV surface characteristics via MBFCM and especially the characterization of the EV-derived miRNA cargo by RNA-Seq to evaluate their potential as biomarkers in AML samples compared to healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples (each tube 0.5 ml) were thawed and subjected to MBFCM (MACSPlex Exosome Kit, human, Miltenyi Biotec). 13,22 EV-containing serum samples were centrifugated at 2500×g for 15 minutes before supernatants were processed. 30 mL of each sample was diluted with 30 mL MACSPlex buffer (MPB) and loaded onto wells of a pre-wet and drained MACSPlex 96-well 0.22 mm lter plate.…”
Section: Ev Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent breakthrough was achieved by combining flow cytometry with imaging optics and CCD camera detection. In a systematic study, Gorgens and coworkers demonstrated the application of imaging flow cytometry (IMFC, commercialised by Luminex/Amnis Image Stream) for robust detection and quantification of EVs down to about 40 nm (Görgens et al., 2019 ), and meanwhile IMFC has seen more widespread use in the EV field (Li et al., 2022 ; Ricklefs et al., 2019 ; Tertel et al., 2022 ). Other approaches available are based on affinity‐capture of EVs on surfaces followed by light microscopy using scattering and/or fluorescence detection by proprietary technologies, such as from NanoView (‘ExoView’) or Oxford Nanoimaging amongst the most advanced implementations ( Nanoview ; Nanoimager ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] Multiplexed assays with up to 39 different antibody‐coated bead populations have also been used for an overall semi‐quantitative analysis of EV surface proteins. [ 44 ] However, this method is only applicable under the prerequisite that the EVs’ surface biomarkers have been identified. The current understanding of EVs populations remains largely unclear due to their heterogeneity and only a few surface markers can be reliably linked to origin cells.…”
Section: Detection Of Extracellular Vesicles Using Optical Read‐out S...mentioning
confidence: 99%